ASYLUM AS A HUMAN RIGHT IN INTERNATIONAL LAW: THEORY AND PRACTICE IN PAKISTAN - Syed Wajdan Rafay Bukhari; Jibran Jamshad; Naila Kareem; Muhammad Waqas Javed; Kashif Mahmood Sadiq (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This article has two parts; first part discusses the asylum as a human right in international law, and second part discusses the law of asylum and procedure in Pakistan. Asylum has no universally accepted definition, but it has three major perspectives attributed to it in International Law. In this study, focus is on asylum as an individual human right. Although Pakistan lacks any specific legislation dealing with asylum system, the study examines and finds Foreigners Act 1946 and Cooperation Agreement 1993 concluded between Pakistan and UNHCR. It may be of a great help envisaging asylum regime in Pakistan. It also highlights how asylum seekers applications are dealt with under Mandate system by UNHCR.